A Paradigmatic Critique of Harold Pinter’s The Caretaker - Dr Ajita Bhattacharya (The Creative Launcher, 2021)
Harold Pinter lived and wrote his plays after the World War period. In this period scholars were associated with the portrayal of unrefined and crude factors of warfare which were, directly and indirectly, related to the people of that time. They also depicted how governments were exploiting common people in the name of safety and warfare. Despite the fact that Pinter’s plays are not actually about warfare or the circumstance of Wars, his plays have the impressions of warfare in various shades. His plays display various levels of human existence. There is an exploration of mental, social, financial, human relationship, and the existential methodology of existence with ludicrousness in his plays. Pinter’s relationship is with the real elements of human existence and activities. He denies the idea of realism in his plays and says that “If you press me for a definition. I would say that what goes on in my plays is realistic, but what I’m doing is not realism” (The Essential Pinter, 11). He always tried to depict concrete and particular idea in his plays through concrete characters. He never wrote his plays for any kind of abstract idea. He is associated with realism in the matter of approach of depiction to the crude and drastic realities of the time. He has represented the post-war British socio-political issues, sensibilities and psychological as well as mental states of the human mind.